Reproductive problems in indigenous cattle at the Ministry of Agriculture farms in central Ethiopia - Bekele, T.; Kasali, O.B.; Takele, G. (1992)
Reports studies on the reproductive performance and its associated problems in indigenous cattle at the Ministry of Agriculture farms in central Ethiopia, at Abernossa and Gobe ranches which are cattle breeding centres of the Ministry of Agriculture. Presents constraints of reproductive performance such as, genital infections, low plane of nutrition and degree of management. Suggests that management interventions particularly nutrition, disease control and destocking would improve reproductive problems.